2008
DOI: 10.1016/j.jvs.2008.03.047
|View full text |Cite
|
Sign up to set email alerts
|

First report of a late type III endoleak from fabric tears of a Zenith stent graft

Abstract: We report a case of a late type III endoleak from a hole in the fabric of the main body of a Zenith bifurcated endograft 7 years after implantation. Abdominal pain and a rapidly expanding aneurysm were eventually followed by rupture. The defect was detected at open surgery, whereas no evidence of endoleak was found at preoperative computed tomography (CT) or angiogram. The defect was repaired by a relining procedure with an Excluder stent graft. The patient, however, died 3 weeks after admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
0
34
1
Order By: Relevance
“…Fabric tear may be more frequent with Z-SG. Although very rare in clinical report, such complication with Z-SG has already been reported (Wanhainen et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Fabric tear may be more frequent with Z-SG. Although very rare in clinical report, such complication with Z-SG has already been reported (Wanhainen et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Type 3b endoleak originates from a defect in the stent-graft fabric and it may be hard to detected with CTA and/or angiography, unless confirmed by open surgery [5,6]. Wanhainen et al [6] firstly reported about late type 3b endoleak diagnosed during the operation, performed due to large retroperitoneal hematoma and intraperitoneal bleeding induced by persistent enlargement of aneurysm sac despite of the embolization of lumbar arteries as a source of suspected type 2 endoleak. Preoperative CTA and emergency angiography could not detect any endoleak except aneurysm expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is the possibility to extend the proximal According to EUROSTAR data, 21,22 the incidence of late type III endoleak after successful EVAR is reported to be ~2% to 3%, and it has been reported with 3 commercially available endoprostheses. [23][24][25] The source of these endoleaks is difficult to identify and often requires multimodal imaging, as demonstrated in the illustrated case ( Figure 2A). Suspected type III endoleaks should be treated promptly, and in an analysis of preliminary EUROSTAR data, patients with late type III endoleaks had 9 times greater chance of aneurysm rupture compared with other registry patients.…”
Section: Discussionmentioning
confidence: 99%